O texto pelo avesso: a gênese das traduções em português da Ilíada - Tatiana Alvarenga Chanoca (2017)
This dissertation is about the genesis of portuguese translations from Iliad done by Odorico Mendes, Carlos Alberto Nunes, Pe. Manuel Alves Correia, Haroldo de Campos and Frederico Lourenço. The study will be guided mainly by texts done by the translators themselves about their own work, and the objective is to find, in this texts the reasons to choose Iliad, the vision each one had about Homer (and Iliad), how was the translation process, what the author wanted with the translation, the books and the mostly consulted works. Will be analyzed and compared editions of theses translations, in order to be able understand if the graphic project of each one is related, somehow, to a published text, or even with the authors proposal, andhow this is done. There is, finally, a reflexion about the adaptations in portuguese, seeking to understand mostly how an why they are done.